ChemInform Abstract: Multicomponent Cascade Reactions of Unprotected Ketoses and Amino Acids — Access to a Defined Configured Quaternary Stereogenic Center. Issue 12 (March 2016) - Richter, Celin; Nguyen Trung, Minh; Mahrwald, Rainer
Abstract: In this stereoselective multicomponent cascade reaction of ketoses with amino acids matched/mismatched situations occur.